The Legal Framework for Personal Data Protection in the Digital Era as Fulfillment of Privacy Rights in Indonesia - Zakaria Said Wachdin, Syarif; Amalina Putri Adytia, Nur; Said, Said (KnE Social Sciences, 2024)
In this digital era, several aspects of our lives are made easier because of the presence and development of technology. One of the examples of it is the creation of various kinds of electronic systems, whether in the form of applications, websites, or portals. In using the systems, the personal data of users is usually required for each of these electronic systems. Personal data is usually used as an identity which is needed to identify a person in the process of the electronic system. Moreover, personal data is considered a sensitive matter since it concludes the information related to a person’s identity, while this information is part of the right to privacy. It is undeniable that a person’s data can be used by irresponsible parties who can harm the owner’s data, especially regarding their privacy rights. Therefore, legal protection is needed for this data, especially in the digital era in which personal data is widely used for various purposes such as electronic systems need or purposes. This study aims to find out and analyze the ideal protection and regulation of legal concepts related to personal data as the fulfillment of privacy rights in the digital era in Indonesia. Keywords: legal framework, personal data, privacy rights